Rekonstruksi Sustainable Teacher Professional Development (TPD) dalam Menghadapi Dominasi Algoritma pada Pendidikan Digital - Hasmi Nur Bayhaqi; Abdulloh Hamid; Moh Faizin (Ashlach : Journal of Islamic Education, 2026)
Objective: This study aims to analyze the implications of algorithmic dominance for teachers’ professional identity and pedagogical agency while reconstructing Sustainable Teacher Professional Development (TPD) to better respond to the complexities of digital education. Methodology: This study employed a qualitative approach using library research and a conceptual-critical design. Data were collected through documentation of academic literature, including international journal articles, scholarly books, research reports, and educational policy documents, and analyzed using qualitative-interpretive content analysis combined with critical-conceptual synthesis. Findings: The findings indicate that algorithmic dominance has transformed the epistemological foundations of education through datafication, automation, and platformization, resulting in shifts in knowledge production, distribution, and validation. These transformations affect teachers’ epistemic authority, pedagogical agency, and professional identity, increasing the risk of pedagogical atrophy and reducing teacher autonomy within data-driven educational environments. Implications: This research implies that teacher professional development programs should move beyond technical digital skills and focus on strengthening algorithmic literacy, critical awareness, pedagogical reflection, and teachers’ capacity to maintain humanistic values in digital learning contexts. Originality: This study contributes to the literature by reconstructing Sustainable Teacher Professional Development from a critical-humanistic perspective and positioning algorithmic dominance as the primary analytical lens, an approach that remains underexplored in previous studies that predominantly emphasize digital competencies and technology integration